Basis of the persistence of capsule-negative Streptococcus suis in porcine endocarditis inferred from comparative genomics. Issue 13 (5th July 2021) - Tohya, Mari; Dozaki, Shinichi; Ishida-Kuroki, Kasumi; Watanabe, Takayasu; Sekizaki, Tsutomu
Abstract: The capsule (cap) of Streptococcus suis is an anti-phagocytic element and is one of the major virulence factors. However, we have found cap-positive and cap-negative isolates in porcine endocarditis. Here, we compared genome sequences of multiple cap-negative isolates with those of a cap-positive isolate from a single endocarditis. Cap-positive and cap-negative isolates from the same pig were phylogenetically closest compared with those from other pigs. Some of cap-negative isolates from the same pig showed different mutations in capsular polysaccharide synthesis ( cps ) genes, suggesting that these isolates arisen in pigs after infection. Different mutations in whole-genomes were also found among isolates with identical mutations in cps genes, indicating that mutations in cps genes and the whole-genome occurred independently. Since cap-negative isolates are rarely found in lesions of other diseases, these results suggest that endocarditis lesions may simply favored cap-negative mutants to survive the niches, leading to their persistence in the lesions. Abstract : Different patterns of mutations in capsule genes were found in cap-negative S. suis isolates from the same porcine endocarditis, indicating that the mutations occurred after infection.